Analysis of Students' Conceptual Understanding Ability on the Material on Polyhedral Shapes - Muhammad Riansyah Rian; Nurhanurawati; Undang Rosidin; Sri Hastuti Noer (Universitas Teknokrat Indonesia, 2025)
This study aims to analyze the level of students' understanding of mathematical concepts systematically. The research sample consisted of thirty ninth-grade studentsof SMP Muhammadiyah 3 Bandar Lampung who were selected through purposive sampling technique. This study employs a quantitative approach, utilizing standardized tests and statistical analysis to measure and analyze the phenomenon in depth. The data used in this study include quantitative data in the form of test results that measure the level of students' understanding of mathematical concepts. Based on the results of the analysis and discussion, it was found that the level of students' understanding of mathematical concepts was still in the low category.